1990
DOI: 10.7863/jum.1990.9.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-aided sonography of the stomach and duodenum in the diagnosis of peptic ulcer disease in adult patients.

Abstract: Sixty-five patients with a clinical suspicion of peptic ulcer disease were evaluated with fluid-aided sonography (US). The results were compared with endoscopic and upper gastrointestinal (UGI) series findings. Fifteen normal volunteers were examined by US only. The stomach and duodenum were both adequately visualized in 12 of the normal volunteers and in 51 of the study patients. US detected wall abnormalities in 21 of 23 patients (91%) with abnormal UGI series and endoscopy in the antropyloric and duodenal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…For example, in a thin patient with a fluid-filled stomach, a layered structure can be imaged in the healthy stomach and in patients with peptic ulcer disease [4]. Water can even be introduced in to the colon by enema to facilitate transabdominal US delineation of pathological thickening as seen in ulcerative colitis or colorectal cancer [5][6][7].…”
Section: Ultrasound Imaging Of the Gi Wallmentioning
confidence: 99%
“…For example, in a thin patient with a fluid-filled stomach, a layered structure can be imaged in the healthy stomach and in patients with peptic ulcer disease [4]. Water can even be introduced in to the colon by enema to facilitate transabdominal US delineation of pathological thickening as seen in ulcerative colitis or colorectal cancer [5][6][7].…”
Section: Ultrasound Imaging Of the Gi Wallmentioning
confidence: 99%
“…However, several authors have reported cases in which abdominal sonography demonstrated indirect and direct signs indicative of PUP, though most of the indirect signs-such as subphrenic and subhepatic fluid collection, fluid accumulation in the lesser omentum, thickening of the gallbladder wall, an inflammatory mass in the upper abdomen, focal or diffuse thickening, and deformity of the wall of the gastric antrum or duodenal bulb-are not specific for PUP. [3][4][5][6] Furthermore, most of these signs can be more accurately demonstrated with CT. 3 However, CT is an expensive procedure, and it is not as widely available as sonography, thus sonography is often used as a first-line imaging modality in patients with abdominal pain. Lee et al 5 first…”
Section: Discussionmentioning
confidence: 99%
“…Sonography revealed many of the signs previously reported by other authors. [3][4][5][6] A diffuse thickening of the wall of the gastric antrum and an echogenic linear band traversing the entire thickness of the anterior wall of the prepyloric antrum was demonstrated. The latter was considered to represent a full perforation of the gastric wall with accumulation of blood clots, debris, and air bubbles, as Tsai et al 6 have previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations